Análise da precisão de técnicas de moldagem de múltiplos implantes com guia multifuncional - Castanharo, Sabrina Maria [UNESP] (2015)
The accuracy fit among implant components can be influenced by several factors, especially laboratory and clinical protocols evolved during the treatment. In order to provide a more reliable implant-prosthetic rehabilitation, several studies have been developed recently to produce casts with higher accuracy. To transfer a correct implant position, and to maintain the original vertical dimension of occlusion (DVO) for the edentulous patients, impression techniques have been used with Multifunctional Templates (MT). The systems (CAD/CAM) have been used to minimize dimensional inaccuracy when transferring the position of the implant fixtures or abutments to working casts. Therefore, the aim of the present study is to compare the accuracy of different techniques using MT by analyzing with optical microscopie ((LEICA QWin - Leica Microsystems, Wetzar, Germany ) and 3D digital images.(scanner Lava Scan ST, 3M ESPE, St. Paul, USA) Methods: Five impression techniques, (n=8 for each technique, with polyvinyl siloxane (SA) (3M/ESPE, Califórnia, USA) and polyeter (PL) were studied; G0: master model, G1: MT with squared non-splinted copings (SA+SU) G2: ST with squared copings splinted with acrylic resin (SA+RP); ; G3: MT with squared coings splinted with acrylic resin and then the acrylic resin were splinted to MT (SA+RP*); G4: MT with squared copings splinted with metal bars (SA+MET); G5: MT with squared copings splinted with metal bars that were splinted to MT with acrylic resin (SA+MET*), and the groups (PL): G6: (PL+SU); G7: (PL+RP); G8: (PL+RP*); G9: (PL+MET); G10: (PL+MET*).. The 3Danalysiswasappliedto: G0, G1, G2, G3, G4 and G5. The software Cumulus (Minnesota Dental Research Center for Biomaterials and Biomechanics, MN, USA) was used to superimpose the cast images scanned by Lava Scan ST (3M ESPE) to calculate the 3-dimensional distances of the spatial discrepancy. The data sowed for ...(Complete abstract electronic access below)